The Essential Roles Training and Supervision of Mental Health Counselors play related to Parent Engagement in Behavioral Health Programs. - Beier, Susanne; Millsap, Cattima; Sienrukos, John (Archives of Business Research, 2019)
Parent engagement in the field of child mental health is gaining an increased amount of support and attention in becoming the catalyst to confronting children’s mental health challenges and outcomes. As parent engagement has become a growing influence in the last twenty-five years in the child mental health field, parents are now realized as allies where they are empowered and becoming inclusive within the decision-making and change process. The paradigm shift has changed itself from parents perceived as the blame for children’s mental health disabilities to parents’ insights and feedback being welcomed to stimulate changes within the child mental health field. Despite the emergence of parents’ say and influence in child mental health services, the issue of engaging families still lingers as a struggle regardless of promising advances in evidence-based treatment methodologies. Mental health counselors feel motionless and stagnate in the engagement process while wrestling with how to confront organizational constraints and barriers impeding the efficacy of parent engagement. Training and supervision have become two critical components for enhancing staff competency and skill-sets to improving the engagement of parents. This article focuses on the importance of providing training and supervision opportunities to mental health counselors to improve the engagement skills of parents within a child behavioral health program.